Impactos de la pandemia covid-19 en el desarrollo turistico en la ciudad de Quevedo, año 2021 - Macias Quito, Gregorio Julian (2021)
In the city of Quevedo, the rate of robberies, assaults, need for work, closures of large projects, low income and demand, have alerted people to be able to emigrate, causing negativity in the process of tourism activities and new tourism projects. entrepreneurship in the canton. The impacts that COVID-19 gives, affects in the way of insecurity and impatience, determining that development in tourist activities and the GDP of the country and Quevedo have declined. The pandemic is a pernicious phenomenon that negatively impacts many areas that it surrounds, but it can be a positive shock if you carefully take advantage of the circumstance. Therefore, an easily understood methodology has been used to collect data and obtain results, the use of the analytical and deductive method has helped in the analysis and collection of paradigms on the impact generated by Covid-19. The negative impacts are greater, but many ventures have manifested themselves as an unfavorable cause of the pandemic, in Ecuador and therefore in the city of Quevedo, people have had to mold themselves in the activities that the COE and the government agents in charge authorize, but In view of the fact that the progress due to Covid-19 in the canton is quite unbalancing, they have chosen to have biosafety measures in the first instance and continue in activities without paralyzing them, some taking risks and others incredulous, but the lack and the adverse impact push to that in one way or another they are carried out, waiting for everything to be favorable. Citizens' contributions and information from important bibliographic sources were taken into account to reach the point of impact and development of the economy and tourism of the city of Rio, the results of the same are presented, where it is declared that the impact is quite balancing currently compared in 2019 and 2020 and that with government help and wise municipal decisions, they will have a positive impact and improve quality.